Incidencia de la calidad de empleo sobre la tasa de ocupación ¿existe una disyuntiva laboral? Evidencia a nivel provincial para Ecuador, durante el periodo 2007-2016 - León Ortega, David Gerardo (2022)
The quality of employment is a phenomenon very little studied at present, especially in developing countries where the generation of work sources is prioritized without considering qualitative aspects such as job satisfaction. In Ecuador, 32.5% of the Población Económicamente Activa (PEA) had an adequate job in April 2022, that is, that 3 out of 10 Ecuadorians have a decent job, with all the benefits of law. Therefore, the study of the quality of employment is essential to know the dynamics of the labor market and evaluate the existence of the dilemma between quality and quantity of jobs. However, this has not been addressed from other perspectives such as the qualities that jobs have in each of the provinces of Ecuador. Which is why, this research aims to study the determinants of job quality and its impact on the employment rate of Ecuador at the provincial level, during the period 2007-2016. The study panel collects information from the Instituto Nacional de Estadísticas y Censos (INEC), the Banco Central del Ecuador (BCE) and the Directorio de Empresas y Establecimientos (DIEE). Thus, the dependent variable is the registered job places, and the explanatory variable is the Índice de Calidad de Empleo (ICE), in addition to the control variables. The methodology used is quantitative and for the construction of the ECI Principal Component Analysis (PCA) is applied, and after that, a Generalized Least Squares (GLS) model is executed. The results indicate that there is no labor dilemma between the quality of employment and the number of jobs, so a dynamic of improvement of working conditions should be promoted so that, in this way, the generation of more work sources is stimulated.